A structured approach to the evaluation of indoor environments'ecological valency. Issue 3 (8th December 2021) - Mahdavi, Ardeshir; Teufl, Helene; Berger, Christiane
Abstract: Buildings typically are expected to provide their inhabitants with the opportunity to influence the indoor environment using various control devices. These include, for example, windows, luminaires, radiators, and shading elements. The quality and adequacy of the indoor environment is thus dependent on the availability and effectiveness of such devices. There is arguably a lack of generally agreed-upon evaluation procedures for this aspect of buildings' indoor environment, namely its controllability by building users, or – in the terminology of Human Ecology – its "ecological valency". In this context, the present contribution explores the possibility to specify buildings' ecological valency in a systematic and reproducible manner. Toward this end, first appropriate theoretical foundations for this purpose are explored and previous related efforts are briefly reviewed. Subsequently, a specific approach toward an ecological valency evaluation method is presented. As part of this approach, five main categories of control devices are documented in various rooms of a building, including windows, shading, lights, heating and cooling systems. Whereas, the first part of this method deals with the basic availability of these control devices and elements, the second part looks at their spatial distribution, effectiveness (both objective and subjective), interface quality (to support user interaction), and ecological quality. The presented evaluation method is tested for six different rooms of an office area in an educational building in Vienna, Austria. Thirty participants independently evaluated this area based on the proposed method and associated protocol. The results point to high degree of congruence between the evaluation results of different participants while judging the principle availability and typology of the control devices. Higher variation was observed in the evaluation of the quality of devices and their interfaces. As a whole, the results suggest that methods similar to the one presented in this contribution may indeed provide an opportunity to extend building performance evaluation procedures beyond energy and cost criteria so as to cover aspects pertaining to user control and satisfaction.